Любимые сказки народов Урала и Поволжья - Гарипов Менсадык Гарипович (Удмуртия, 2022)
Экземпляры: ф.10 (20230417) / Инвентарный номер: 63348 / Цена: / Сис.шифр: 82.3(235)-6 / Авт.знак: Л 93 / ГРНТИ: 17.71.91 / ББК: 82.3(235)-6